Trypanocide Treatment of Women Infected with Trypanosoma cruzi and Its Effect on Preventing Congenital Chagas - Fabbro, Diana L.; Danesi, Emmaria; Olivera, Veronica; Codebó, Maria Olenka; Denner, Susana; Heredia, Cecilia; Streiger, Mirtha; Sosa-Estani, Sergio (PLOS Neglected Tropical Diseases, 2014)
Author Summary Congenital infection with Trypanosoma cruzi is the most common mode of transmission in countries where the vectorial and transfusional routes have been controlled. We evaluated the efficacy of trypanocidal therapy in preventing congenital Chagas disease and compared the clinical and serological changes between treated and untreated mothers. From medical records of infected women with and without trypanocidal treatment, we studied their children to detect congenital infection. Among 222 children of untreated mothers, we detected 34 cases of congenital transmission. The 132 children of previously treated women were born without infection. In 117 mothers followed for more than eight years, we observed negative serology for Chagas in 43.7% of the treated women and none in untreated mothers. Regarding their clinical course, there was also a positive difference for treated women (2.2%), compared with untreated ones (15.4%). These results indicate the benefit of providing etiologic treatment to young people with chronic infection. This recommendation would have a major health impact both in primary prevention, preventing further cases of congenital Chagas disease, and in secondary prevention, reducing the risks of morbidity and mortality that can cause infection.